Smartphone sensors and video analysis: two allies in the physics laboratory battle field. Issue 1 (May 2021) - Monteiro, M; Cabeza, C; Stari, C; Marti, A C
Abstract: Recently, two technologies: video analysis and mobile device sensors have considerable impacted Physics teaching. However, in general, these techniques are usually used independently. Here, we focus on a less-explored feature: the possibility of using supplementary video analysis and smartphone (or other mobile devices) sensors. First, we review some experiments reported in the literature using both tools. Next, we present an experiment specially suited to compare both resources and discuss in detail some typical results. We found that, as a rule, video analysis provides distances or angular variables, while sensors supplies velocity or acceleration (either linear or angular). The numerical differentiation of higher derivatives, i.e. acceleration, usually implies noisier results while the opposite process (the numerical integration of a temporal evolution) gives rise to the accumulation of errors. In a classroom situation, the comparison between these two techniques offers an opportunity to discuss not only concepts related to the specific experiment but also with the experimental and numerical aspects including their pros and cons.